Developing Communicative Language Test for Vocational Senior High School - Defrioka, Andri (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2007)
This paper is aimed at revealing the role of communicative language test n enabling and measuring studentâ€™s English achievement at Vocational School (SMK). Its coverage will be the considerations and procedures to construct communicative language test. This test is intended to be a measure of how the testees are able to use language in real life situations. There are several models of communicative competence, grammatical competence, sociolinguistic competence, discourse competence, and strategic competence. This test has three steps; identifying objectives, developing the test, specification, and developing the communicative test. Â  Key Words: Communicative test, vocational school, linguistics, sociolinguistics, discourse, strategic,